Statistical evaluation of conduciveness in Sadd al-Dharaʾiʿ: an analytical study - Mustafa Mat Jubri Shamsuddin, (Pusat Penyelidikan Syariah, Fakulti Pengajian Islam, Universiti Kebangsaan Malaysia, 2024)
This analytical study explores the potential of statistical methods for evaluating conduciveness in sadd al-dharāʾiʿ, addressing the current lack of quantitative approaches in this principle of Islamic jurisprudence. The research employs a qualitative methodology, conducting a review of primary Islamic texts and literature, contemporary academic publications, and relevant fatwas. Through content analysis, comparative analysis, and conceptual analysis, the study develops a preliminary framework for statistical evaluation of conduciveness in sadd al-dharāʾiʿ. Key findings reveal that integrating statistical techniques with traditional Islamic legal reasoning can enhance objectivity and precision in assessing the likelihood of permissible actions leading to prohibited outcomes. The proposed framework incorporates steps such as data collection, validation, statistical analysis, and interpretation, all aligned with Islamic legal principles. Analysis of contemporary fatwas and hypothetical case studies demonstrates the framework's potential for providing more nuanced, evidence-based assessments of complex issues. The study concludes that while statistical evaluation offers significant benefits, it must be carefully balanced with traditional scholarship and ethical considerations to maintain consistency with the objectives of Islamic law.